(3GdMeGjI GdLfGFjI dSjQ GdGeJMGfGJ (B/s - (3GdeQGZj, CMeO YHO GddGgs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2019)
(3jJfGhd cJGH (B((3GdMeGjI GdLfGFjI dSjQ GdGeJMGfGJ(B) (3hGdPj bGe HJCdjag (B((3GdOcJhQ CMeO YHO GddGg YHO GdMejO YHO GdQMje GdeQGZj(B) (3aj MhGdj (B(403) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdZT aj GdGeJMGfGJ(B) (3GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3XGgQJj GdZT aj GdGeJMGfGJ hJSQjHgG hCKQgeG Ydi GdENdGd HGdGeJMGfGJ, GdaUd GdKGfj (B: (3GdSjGSI GdLfGFjI dehGLgI GdENdGd HGdGeJMGfGJ (B... (3EdN(B.s
(3GdeMJhjGJ (B: (3GdaUd GdChd (B: (3XGgQJj GdZT aj GdGeJMGfGJ hJSQjHgG hCKQgeG Ydi GdENdGd HGdGeJMGfGJ(B-(3GdeHMK GdChd (B: (3GdZT aj GdGeJMGfGJ Hjf GdNWC GdJCOjHj hGdLQjeI GdLfGFjI(B-(3GdeHMK GdKGfj (B: (3JWHjb bGfhf ecGaMI GdENdGd HGdGeJMGfGJ(B-(3GdaUd GdKGfj (B: (3GdSjGSI GdLfGFjI dehGLgI GdENdGd HGdGeJMGfGJ(B-(3GdeHMK GdChd (B: (3GdLQGFe GdhGQOI aj GdbGfhf Qbe (B73 (3dSfI (B2017-(3GdeHMK GdKGfj (B: (3GdSjGSI GdYbGHjI dehGLgI GdENdGd HGdGeJMGfGJ(B.s
(3edGMb (B: (3UaMI (B395-400.s
(3HHdjhLQGajI (B: (3UaMI (B311-393.s
Keywords: (3GdJYdjes -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdZT aj GdGeJMGfGJs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdGeJMGfGJs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3JSQjH GdGeJMGfGJs; (3GdSdhc GdELQGej s